Understanding forensic digital imaging - Blitzer, Herbert L.; Stein-Ferguson, Karen; Huang, Jeffrey; Jacobia, Jack (Academic Press, 2008)
Offers the principles of forensic digital imaging and photography. This title provides information on how to photograph any setting that may have forensic value, details how to follow practices that are acceptable in court, and recommends what variety of hardware and software are most valuable to a practitioner.